PRAGMATIC FEATURES OF INTERROGATIVE CATEGORY IN UZBEK AND ENGLISH (Conference Zone, 2022)
The article enlightens the issues of studying pragmatic and grammar peculiarities of interrogations in Uzbek and English languages.